A brief overview of the registration system of radiation exposure doses for decontamination workers and their occupational health management. Issue 1 (8th September 2022) - Fukunaga, Hisanori; Asano, Tomohiro
Abstract: Following the Fukushima nuclear accident in March 2011, decontamination and related works have been carried out over a wide area, mainly in Fukushima Prefecture. In November 2013, the Radiation Dose Registration and Management System for Decontamination Workers was established to manage the occupational exposure doses of workers engaged in such work. The Radiation Effects Association mainly operates the registration system. This paper summarizes existing reports on this system and occupational health issues among decontamination workers. We collected previous reports and related regulatory laws on occupational health management for decontamination workers working in Fukushima Prefecture, summarized the outline of the radiation dose registration and management system for these decontamination workers, and discussed future issues related to their health management. Approximately 100 000 decontamination workers were registered in the system as of 2020, but none showed radiation doses that exceeded the dose limit. To our knowledge, there have been no reports of decontamination workers presenting physical symptoms suspected to be related to radiation exposure. On the other hand, heatstroke countermeasures and anxiety about radiation exposure have been reported as possible issues in the occupational health management of decontamination workers. Although decontamination workers are unlikely to experience biological effects from radiation exposure, epidemiological studies are needed to examine this evidence. Further analysis is also needed on non‐radiation effects, which pose occupational health concerns for decontamination workers. The registration system would allow for tracking decontamination workers, providing data for analyzing radiological and non‐radiological effects.